Effectiveness of shielding in computed tomography examinations - Coelho, Soraia (2022)
Computed Tomography (CT) is an important tool in providing high-quality crosssectional images of the body using ionizing radiation and computational reconstruction techniques. CT has transformed much of medical imaging by providing three-dimensional views of the organ or body region of interest. CT involves larger radiation doses than the more common, conventional x-ray imaging procedures, and technological developments have contributed to the increase of number and diversity of scanning procedures, in adults and pediatrics patients. Since an increasing number of CT scans are being obtained, the...